Ethical challenges among registered dietitians in oral nutritional supplement prescription - Pohjola, Susanna (Nursing ethics, 2026)
Background Ethical considerations are an inherent part of all clinical decision-making, yet the specific ethical challenges faced by registered dietitians [RDs] remain underexplored.Aim Explore RDs ethical challenges in oral nutritional supplement prescription [ONS].Research Design A qualitative descriptive research design.Participants and Research Context Thirteen RDs working in Swedish primary care (n = 7) and hospital settings (n = 6) were recruited via purposive sampling through the professional association. Data were collected through individual semi-structured interviews (Oct 2019?Apr 2020) and analyzed using systematic text condensation [STC], containing four iterative steps.Ethical Considerations The Swedish Ethical Review Authority [Reference No. 2019-01198 and 2023-06903-02] approved the study protocol and all participants provided written informed consent.Findings Through STC, two main categories were identified: (1) Structural prerequisites for equitable and accessible care and (2) Navigating professional judgment and the patient?s wishes. Registered Dietitians described ethical challenges related to justice, such as patients in rural areas lacking transport to care facilities or ONS home delivery. Autonomy-related challenges involved persuading vulnerable patients who were dependent on others for nutrition support. Registered dietitians also faced ethical challenges related to beneficence and non-maleficence, when balancing ONS prescription with concerns about replacing regular meals.Conclusions Registered dietitians described ethical challenges, such as discomfort due to financial or systemic barriers, and using paternalistic persuasion. These challenges may lead to moral distress, highlighting the need for ethics support to reduce distress and promote well-being. Healthcare systems should also ensure equitable access and clarify ONS prescription guidelines.